2021
DOI: 10.1002/jdd.12541
|View full text |Cite
|
Sign up to set email alerts
|

Hands‐on live demonstration vs. video‐supported demonstration of an aesthetic composite restoration in undergraduate dental teaching

Abstract: Purpose/Objectives: Live hands-on demonstration of dental procedures is a central format in undergraduate dental teaching. It captures the immediacy of the clinical situation and allows for direct communication between instructor and students, but it also requires an experienced instructor who is able to handle both the performed treatment and its visualization alongside the actual teaching. The aim of the present work is to compare the hands-on demonstration of a class IV composite restoration to a teaching f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 22 publications
1
11
0
2
Order By: Relevance
“…Moreover, experience from undergraduate dental teaching shows that changes in procedures at dental schools are rather infrequent. 28 Therefore, welldesigned video-based materials, once produced, may be used for teaching for an acceptable period of years/courses to weigh-out the resources spent on the development and production. The present work, however, suggests that the production of procedural videos for the exclusive use during lectures is not worth the effort.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, experience from undergraduate dental teaching shows that changes in procedures at dental schools are rather infrequent. 28 Therefore, welldesigned video-based materials, once produced, may be used for teaching for an acceptable period of years/courses to weigh-out the resources spent on the development and production. The present work, however, suggests that the production of procedural videos for the exclusive use during lectures is not worth the effort.…”
Section: Discussionmentioning
confidence: 99%
“…1,2,4, 16,22,26,30 Other studies in the field of dentistry have based their evaluation of teaching methods on students' answers in questionnaires. 15,25,28 One may argue that the chosen evaluation method introduces a possible bias due to the Dunning-Kruger effect. 31 The Dunning-Kruger effect is defined as an overestimation of own skills and abilities (inflated self-assessment) by persons inexperienced in the field.…”
Section: Discussionmentioning
confidence: 99%
“…De acuerdo con lo encontrado en este estudio, parece ser que la demostración con video en vivo es un recurso didáctico que no favorece el aprendizaje centrado en el estudiante, sino que más bien se centra en el rol o performance del docente. Esto se correlaciona a lo observado por Schlafer et al, (2020) en estudiantes de pregrado de la Universidad de Aarhus (Dinamarca), quienes compararon la demostración con video en vivo y la entrega de un video pregrabado con el procedimiento a simular y encontraron que la discusión grupal y la interacción con el docente fue más activa en aquellos estudiantes que recibieron la demostración con la modalidad de video pregrabado. En este sentido es necesario, dentro de los ámbitos de demostración, avanzar desde la observación pasiva de procedimientos odontológicos simulados hacia observación activa, en dónde, si la participación activa del estudiante en la demostración no es posible, se les debe entregar alguna tarea para llevar a cabo, por ejemplo, dar un espacio de discusión o análisis de cada paso dentro de la secuencia del procedimiento (Babin et al, 2019b).…”
Section: Discussionunclassified
“…With the development of information technology, some practical demonstrations can use livetransmitted hands-on demonstration videos, and prerecorded procedural videos to present specific operating procedures. However, these methods reduce the direct contact between teachers and students, and also lead to the possibility of the loss of fruitful discussion compared with the live demonstration teaching approach [18]. Schlafer et al, (2021) [18] also found that procedural videos that capture all aspects of a teacher's processing in high definition can help in the classroom.…”
Section: Introductionmentioning
confidence: 99%
“…However, these methods reduce the direct contact between teachers and students, and also lead to the possibility of the loss of fruitful discussion compared with the live demonstration teaching approach [18]. Schlafer et al, (2021) [18] also found that procedural videos that capture all aspects of a teacher's processing in high definition can help in the classroom. Thus, this study proposed two types of practical performance anxiety: practical performance anxiety in online courses without hands-on demonstration (PPAOC-without-HD) and practical performance anxiety in online courses with hands-on demonstration (PPAOC-with-HD).…”
Section: Introductionmentioning
confidence: 99%